Making connections - a free-motion quilting workbook : 12 design suites for Longarm or domestic machines / Dorie Hruska - Hruska, Dorie1969-
Streamline your free-motion quilting with this workbook full of exercises to build your skills. Step-by-step illustrations for each design suite show how to adapt the design for blocks, borders, sashing, and allover quilting, while landscape-style format lies flat by your machine. Practice each design on the included practice pages before stitching by machine, then put your skills to work on a gorgeous pieced sampler. Creative designs can be used on both longarm and domestic machines